Controllable Modulation of Efficient Phosphorescence Through Dynamic Metal‐Ligand Coordination for Reversible Anti‐Counterfeiting Printing of Thermal Development. (6th November 2022) - Dai, Wenbo; Li, Gengchen; Zhang, Yongfeng; Ren, Yue; Lei, Yunxiang; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Dong, Yuping
Abstract: Dynamically tunable room‐temperature phosphorescence (RTP) organic materials have attracted considerable attention in recent years due to their great potential over a wide variety of advanced applications. However, the precise regulation of the intersystem crossing (ISC) process for efficient RTP materials with dynamically modulated properties in a rigid environment is challenging. Herein, an effective strategy for RTP material preparation with controllably regulated properties is developed via the construction of dynamic metal‐ligand coordination in a host‐guest doped system. The coordination interaction promotes ISC and phosphorescence emission of the guest, thus allowing the modulation of the photophysical properties of doped materials by changing the doping ratio and Zn 2+ counterions. By taking advantage of the reversible metal‐ligand coordination interaction, the coordination‐activated, and dissociation‐deactivated RTP is dynamically manipulated. With the unique Zn 2+ ‐responsible RTP enhancement materials, the anti‐counterfeiting applications of thermal development, and color inversion have been constructed for inkjet printing of high‐resolution patterns with high reversibility for many write/erase cycles. The results show that dynamic metal‐ligand coordination strategy is a promising approach for achieving efficient RTP materials with controllably modulated properties. Abstract : An effective strategy for room‐temperature phosphorescence (RTP) material preparation with controllably regulated properties is developed via the construction of dynamic metal‐ligand coordination in a host‐guest doped system. Based on the reversible metal‐ligand coordination interaction, the coordination‐activated and dissociation‐deactivated RTP is dynamically manipulated. The anti‐counterfeiting applications of thermal development related to the unique Zn 2+ ‐responsible RTP enhancement mechanism is realized for the first time.